A bicyclic unit reversal to stabilize the 12/14-helix in mixed homochiral oligoureas. Issue 57 (12th June 2020) - Milbeo, Pierre; Simon, Matthieu; Didierjean, Claude; Wenger, Emmanuel; Aubert, Emmanuel; Martinez, Jean; Amblard, Muriel; Calmès, Monique; Legrand, Baptiste
Abstract : Incorporation of highly constrained building blocks into oligoureas: a simple bicycle reversal leads to tunable 12/14-helices formation. Abstract : The insertion of cyclic building blocks in oligoureas to stabilize or modulate the properties of the 12/14-helix was often fruitless. We herein propose a fully compatible highly constrained building block that could be incorporated into oligoureas to develop highly stable and functional oligoureas helices.